If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15(3m + 10) = 0 Reorder the terms: 15(10 + 3m) = 0 (10 * 15 + 3m * 15) = 0 (150 + 45m) = 0 Solving 150 + 45m = 0 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-150' to each side of the equation. 150 + -150 + 45m = 0 + -150 Combine like terms: 150 + -150 = 0 0 + 45m = 0 + -150 45m = 0 + -150 Combine like terms: 0 + -150 = -150 45m = -150 Divide each side by '45'. m = -3.333333333 Simplifying m = -3.333333333
| 5x+6=-4+3x+20 | | 3+65x=39x+21 | | 20=x*5 | | 16x+11=47+7x | | f(x)=-6x+18 | | 3x/3=14/3 | | (x-1)(x-2)(x-3)(x-4)+15=0 | | 387.76=190+0.96x | | 3x+10=-53-6x | | a+6=3a+8 | | x+9=x+6 | | -1.6(2y+15)=-1.2(2y+23) | | 3x-1=1-x | | 3x+2x-x=11x+9 | | (2x-2)^2/3=16 | | 1+7x=13x+x | | 24x=314 | | 3-2(x+3)=-7 | | 9w-15=7w+5 | | 3x+6+5=x+10+x | | -7x+3=25 | | -6+-2x=-4x+-4 | | 7x-1=x-4 | | 4t-9=12+11t | | -6+-2x=-4x | | 3x-6+6=8+6 | | 12/x-3=6/2x | | 2y-5+5y-9= | | 11x-8=9x-16 | | x-4=x-6 | | 3+xi=(x+1)+2 | | 8x-5(2x-8)=42-3x |